Să fie lumină! (Fac 1, 3) în înțelegerea Luminii Primordiale - Chirilă, Ioan (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The concept of light occupies a prominent place in most religions and cultures and can be understood both at a literal and a metaphorical level. Ever since antiquity, people have created and, later on, have developed a mutual connection between light and divinity. Noticing that the sun was the one that provided them with light, the people of ancient times came to attribute human qualities to the light in the sky and to serve it. Unlike them, the hagiographers specified from the very first book of the Holy Scripture that light is God’s creation (Gen. 1:3-5; Is. 45:7) and that it differs significantly from the lights in the vault of the sky (Gen. 1:14-18). The light made by God on the first day of creation to give light to the world is different from the natural light that the sun and the moon shed. Prophet Isaiah underlines this distinction, foretelling a time when the sun will no longer have to shine during the day, as God Himself will be an everlasting light for man (Is. 60:19-20; acc. Rev. 21:23; 22:5). In other words, the Old Testament grants a deep theological dimension to the primordial light, highlighting the fact that its radiance is due to God and that it cannot exist separately from Him. Thus, in this study we shall demonstrate that the uncreated light which was commanded into being by God is nothing else than the radiance of God’s glory and, implicitly, a manner of revealing the mystery of the uncreated light that overflew the world from the very first day of the text of creation.